Pendekatan TOGAF-ADM dalam Penerapan Cloud Computing untuk Integrasi Arsitektur Sistem Informasi - Raden Deden Ahmad Hidayat (CV. ULIL ALBAB CORP, 2024)
The need to be able to access medical record data of TNI AU Hospital patients who are medically registered at other TNI AU Hospitals becomes a major problem when TNI AU staff are on duty. Doctors need fast medical information when they have to treat TNI AU patients who are sick or injured in carrying out their duties. Meanwhile, Disinfolahtaau, which is a work unit responsible for the development of information systems, faces the need to carry out system integration related to the hospital information system it is developing. This research focuses on the topic of cloud computing as an internet technology that can overcome this problem. Togaf-ADM is a method used to model enterprise IT architecture, the TNI AU hospital business process is the scope of this research with a number of stakeholders. The results of the study have been able to identify 3 (three) entities and 2 (two) applications that are needed as a system development model. Web services technology with XML is the technology architecture needed by the system, and batch integration with an import-export mechanism was found as a new business process for the TNI AU Hospital Information System model based on Cloud)